Tafsir Bil-Ma’tsur (Konsep, Jenis, Status, dan Kelebihan Serta Kekurangannya) - Abu BakarAdnan Siregar (Sekolah Tinggi Agama Islam Sumatera Medan, 2018)
The purpose of writing this article is to further analyze the Tafsir bi al-Ma’tsur: concepts, types, status, advantages and disadvantages. The method of writing this article is qualitative - descriptive that uses authentic sources. It can be seen that the Tafsir bi al-Ma’tsur is the greatest type of interpretation if the sanad reaches the Prophet Muhammad or the friend. However, the Tafsir bi al-Ma’tsur still needs history. Ibn Katsar said: